Higher-level cognitive functions in Dutch elite and sub-elite table tennis players - Elferink-Gemser, M. T.; Faber, I. R.; Visscher, C.; Hung, T.-M.; de Vries, S. J.; Nijhuis-van der Sanden, M. W. G. (PLOS ONE, 2018)
This study aimed to investigate the higher-level cognitive functions (i.e. metacognition and executive functions) of Dutch competitive table tennis players to better understand its relevance for performance in this fast and complex sport. Thirty elite (age 16 ± 4) and thirty age and sex-matched sub-elite peers (age 16 ± 5) were assessed on metacognition and executive functions (working memory, inhibitory control, cognitive flexibility) using D-KEFS tests. Compared to norm scores, both the Dutch competitive elite and sub-elite table tennis players scored above average on all tests (p < 0.05). MANOVA showed a main effect for performance level (elites outscored sub-elites; p < 0.05). T-tests revealed that elite players make less mistakes on tests for inhibitory control (CWI-3: 0.9 ± 0.9; CWI-4: 1.1 ± 1.2) than sub-elite players (CWI-3: 1.8 ± 1.1; CWI-4: 2.6 ± 1.5) (p < 0.05). When controlling for training hours in a MANCOVA, no significant main effect of performance level remained (p > 0.05). In conclusion, Dutch elite and sub-elite table tennis players are characterized by above-average scores on higher-level cognitive functions compared to norm scores. A relation with performance level has been shown, which may be explained by the greater exposure to table tennis for elite compared to sub-elite players. However, longitudinal research is needed to indicate the direction of this association